Nitrate–Nitrite–Nitric Oxide Pathway, Oxidative Stress, and Fertility Outcomes in Morbidly Obese Women Following Bariatric Surgery: A Systematic Review - Charalampos Voros; Despoina Mavrogianni; Aspasia Minaoglou; Alexios Karakasis; Anthi-Maria Papahliou; Vasileios Topalis; Antonia Varthaliti; Raphail Mantzioros; Panagiota Kondili; Menelaos Darlas; Regina Sotiropoulou; Diamantis Athanasiou; et al. (Biomedicines)
Obesity reduces nitric oxide (NO) production due to endothelial nitric oxide synthase (eNOS) dysfunction, resulting in oxidative stress, mitochondrial dysfunction, and chronic inflammation. These factors have a negative impact on reproductive health, including oocyte quality, endometrial receptivity, and embryo implantation. When oxidative stress affects eNOS function, the nitrate–nitrite–nitric oxide (NO3-NO2-NO) pathway provides an alternate route for NO production. Bariatric surgery has been found to restore NO production, reduce oxidative stress, and improve fertility in morbidly obese women. This review investigates the molecular mechanisms by which bariatric surgery affects eNOS activity, the NO3-NO2-NO pathway, and oxidative stress reduction, with an emphasis on intracellular activities including mitochondrial biogenesis and NO production. A systematic review employing PRISMA criteria included articles published between 2000 and 2024 from PubMed, Scopus, and Embase that investigated NO3-NO2 pathways, oxidative stress markers, hormonal alterations, and reproductive outcomes in morbidly obese women following bariatric surgery. After evaluating 1542 studies, 11 were selected for the final analysis. Results showed a 45% increase in NO3-NO2 levels (p < 0.001), a 35% reduction in oxidative stress indicators (p < 0.01), a 60% increase in pregnancy rates, and a 50% increase in spontaneous ovulation rates following surgery. These benefits were connected to improved mitochondrial function and endometrial receptivity as a result of reduced oxidative stress and inflammation. The NO3-NO2-NO route is critical in compensating for lower NO generation under oxidative stress and hypoxia, and bariatric surgery significantly improves this pathway to optimize blood flow, mitochondrial function, and reproductive results.